The vagus nerve-dependent lung-brain axis mediates brain demyelination following acute lung injury - Dan Xu; Mingming Zhao; Guilin Liu; Tingting Zhu; Yi Cai; Rumi Murayama; Yong Yue; Kenji Hashimoto (Brain, Behavior, & Immunity - Health)
Patients with acute lung injury (ALI) often experience psychiatric and neurological symptoms; however, the precise underlying mechanisms remain unclear. Given that white matter loss (demyelination) contributes to these symptoms, we investigated whether lipopolysaccharide (LPS)-induced ALI leads to brain demyelination via a vagus nerve-dependent lung-brain axis. A single intratracheal injection of LPS caused severe lung injury and demyelination in the corpus callosum (CC) of mouse brains. Subdiaphragmatic vagotomy did not affect LPS-induced lung injury or demyelination in the CC. Interestingly, cervical vagotomy significantly attenuated LPS-induced hypo-locomotion, plasma interleukin-6 levels, and demyelination in the CC of ALI mice without influencing lung injury. These findings demonstrate that ALI can induce demyelination in the CC of the mouse brain via a cervical vagus nerve-dependent lung-brain axis, highlighting the critical role of this pathway in the psychiatric and neurological symptoms observed in ALI patients.